Crack engineering boosts the performance of flexible sensors. Issue 5 (2nd September 2022) - Zhou, Yunlei; Lian, Haoxiang; Li, Zhenlei; Yin, Liting; Ji, Qian; Li, Kan; Qi, Fei; Huang, YongAn
Abstract: With exceptional performance, flexible sensors have found broad applications, including human health monitoring, motion detection, human–machine interaction, smart wearable technology, and robot control. Crack‐sensitive structures based on animal bionics have also caught increasing attention because of their extraordinary sensitivity. Crack‐based flexible sensors, which combine the flexibility of the flexible sensors and the high sensitivity of the crack sensing structures, have seen rapid development in recent years. In this review, we summarize the sensing mechanisms of the flexible sensors based on the crack disconnection–reconnection process. The effects of crack type, depth, and density on sensor performance are explored in detail. We also discuss the performance characteristics and applications of the crack‐based flexible sensors with various materials, design structures, and crack generation procedures. Finally, the main challenges of the crack‐based flexible sensors are also reviewed, and several research directions are proposed. Abstract : The integration of the advances from various fields to the crack design has made significant progress in the development of flexible sensors. In this review, the applications of crack engineering in strain sensors, pressure sensors, temperature sensors, magnetic field sensors, hydrogen sensors, and other sensors are summarized. The crack formation mechanism and sensing mechanisms of these sensors are discussed, and the influence of fabrication methods and material on crack construction are examined in detail.